Meanings & Co. The Interdisciplinarity of Communication, Semiotics and Multimodality - Olteanu, Alin.; Stables, Andrew; Borţun, Dumitru; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book explores the interdisciplinarity of semiotics and communication studies, comprising both theoretical explorations and semiotic applications to communication with theoretical bearings. These disciplines have generally been understood as mutually implicit, but there still are many unexplored research avenues in this area, particularly on a conceptual level. The book offers broad insights into the epistemological relations between semiotics and other approaches to communication from perspectives such as sociology, philosophy of language and communication theory. As such, it sheds light on the communication of knowledge. Semiotics is currently enjoying increasing popularity within the humanities and social sciences. Understood as relational logic (Charles Peirce) or hermeneutics (structuralism and poststructuralism), semiotics fundamentally implies certain positions with regard to communication. Because of the generality and conceptual vagueness of semiosis and communication, how one elucidates the other is still an underexplored theme. With some pioneering studies of this relation, the books examines various fields, such as language, code, learning, embodiment, political communication, media, cinema, cuisine, multimodality and intertextuality.
Introduction -- The problem of code in semiosis and communication -- Modelling Human Communication: Mediality and semiotics -- Exploring a semiotic conceptualisation of modelling in digital humanities practices -- Rationality and Reasobleness in Textual Interpretation -- The Body/Tongue Analogue: mimesis, embodiment, and the coevolution of language in biosemiotic perspective -- Multimodal propositions and metaphors in the movie Submarine: an application of Peirce's doctrine of Dicisigns -- The 'Multi-mode transitional practice' of storytelling while work is done -- Performer as Meaning-Generator: An Application of Gino Stefani's Theory of Musical Competence -- Translation of Culture-Specific Items in Menus -- Food politics and the metalevels of carnism -- Semiotic Approach to Communication. The Secondary Game and the Secret of Power on People -- Semiotic Practices in TV Debates -- Racism and Classisim in Mexican Advertising. An Exhibition of Visual Messaging.
Keywords: Semiotics; Communication; Language and languages -- Philosophy; Biology -- Philosophy; Communication in politics; Semiotics; Media and Communication; Philosophy of Language; Philosophy of Biology; Political Communication